(untitled) (Palimpsesto, 2021)
This article studies the journal El Pizarrón, which is analyzed from the reading of its editions and interviews with members of its editorial committee. El Pizarrón represented the most important educational publication of the opposition to the Augusto Pinochet dictatorship and its pedagogical, political and union motivations were linked to the ideological renewal process that Chilean socialism experienced during the 1980s. The above was translated mainly in a turn given by the magazine regarding the role that the State and the private sector should assume in the educational administration, as well as regarding the most appropriate organizational structure for Chilean teachers.